Mencari Jalur K Terpendek Menggunakan Yen Algoritm Untuk Multipath Routing Pada Openflow Software-Defined Network - Afredy Carlo Sembiring; Wijaya Kurniawan; Widhi Yahya (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
SDN (software defined network) is a separate network model between control plane and data plane using Openflow communication protocol standard to connect the two. Software defined network developed in recent years and has done many implementation one of them is for network routing. There are three routing algorithms in this research are Yen algorithm DFS algorithm and Dijikstra algortime. For three algortime it will be implemented using mininent and ryu controller. This test is performed to see the performance of the algorithm includes throughput, convergence time and packet loss. After testing from convergence time, Yen algorithm get an average of 0.0070 seconds and DFS of 0.00734 seconds. After getting the data on the test using the yens algorithm then it will be compared with the data obtained using DFS algorithm and Djkstra algorithm with the same method. Based on throughput results, Yen Algorithm outperformed the DFS algorithm and Dijkstra's algorithm with an average of 178,422. In packet loss test yens algorithm, dfs and dijkstra, here yens have a smaller loss packet compared with dfs and dijkstra.